TikTok and Mental Health Communication: Exploring Content and Public Engagement - Mawaddah, Mawaddah; Maharani, Blangi Intan (Universitas Persada Indonesia YAI, 2025)
This study aims to explore communication styles and public engagement levels in mental health-related content on the TikTok platform. The growing openness in discussing mental health issues on social media reflects a shift in how society perceives and responds to topics once considered taboo. Employing a descriptive qualitative approach, the research combines content analysis of popular TikTok videos tagged with #mentalhealth and an online survey to assess user perceptions and content representation. The findings reveal that most content employs a casual tone with emotional and motivational delivery. Visuals tend to be minimalistic but support a reflective narrative atmosphere, often accompanied by melancholic background music. Content creators include both professional psychologists and individuals sharing personal experiences. Public engagement is notably high, as indicated by significant numbers of likes, comments, and shares, with predominantly positive and empathetic responses. These results affirm that TikTok serves not only as a space for entertainment but also as an effective medium for mental health communication—provided it is supported by adequate media literacy to prevent misinformation. The study recommends fostering collaboration between mental health professionals and content creators to build a healthier and more educational digital ecosystem.